Pengaruh Kompensasi Terhadap Kinerja Karyawan Pada PT Bank Negara Indonesia Tbk. Cabang Tanjung Redeb - Ardiansyah, Ardiansyah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:The purpose of this study is to analyze and find out more about the effect of compensation on employee performance at PT Bank Negara Indonesia Tbk. Tanjung Redeb Branch. The research data comes from questionnaires distributed to 73 respondents who are employees of PT Bank Negara Indonesia Tbk. Tanjung Redeb Branch, using the census method. The analytical tool used is the validity test, reliability test, simple linear regression equation, coefficient of determination and t test.The results of this study indicate that the compensation regression coefficient is positive at 0.563, which means that between compensation and employee performance has a unidirectional relationship. If there is an increase in compensation value then it will have a positive influence on improving employee performance at PT Bank Negara Indonesia Tbk. Tanjung Redeb Branch. Compensation has a significant effect on employee performance at PT Bank Negara Indonesia Tbk. Tanjung Redeb branch, evidenced from the results of the t test where the value is calculated> t-table value (4.076> 1,994) and significance value <probability value (0,000 <0,05). So it was decided to accept the hypothesis in this study. The coefficient of determination illustrates that employee performance variables are only able to explain the variable performance of employees at PT Bank Negara Indonesia Tbk. Tanjung Redeb Branch is 19.0%, while the remaining 81.0% is explained by other factors not included in this study.Keywords: Compensation, Employee Performance